2013
DOI: 10.3892/ijo.2013.2073
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MMP-9 using a pyrrole-imidazole polyamide reduces cell invasion in renal cell carcinoma

Abstract: Abstract.We investigated the clinical significance of the expression levels of matrix metalloproteinase 9 (MMP-9) in renal cell carcinoma (RCC). In addition, we validated the efficacy of pyrrole imidazole polyamide (PIP) targeting MMP-9 on inhibiting proliferation and invasion of RCC. We evaluated the expression levels of MMP-9 in 249 RCC specimens by immunostaining and analyzed the association between MMP-9 expression levels and cancer-specific survival. Furthermore, in a human RCC cell line, Caki-2, we teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 21 publications
1
16
0
1
Order By: Relevance
“…A previous report indicated that substantially higher MMP‐9 protein expression was observed in RCC tumors than in normal tissues, but no difference was observed in MMP‐2 expression . MMP‐9 could be a critical molecule for RCC invasion and metastasis not only because this MMP type destroys type IV collagen, a major component of the basement membrane , but also because type IV collagenase activity is a key determinant of the in vitro invasiveness of RCC cells and their metastatic potential . Our results are consistent with those of previous studies, which have indicated that MMP‐9 is a critical target of melatonin for regulation of RCC metastasis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A previous report indicated that substantially higher MMP‐9 protein expression was observed in RCC tumors than in normal tissues, but no difference was observed in MMP‐2 expression . MMP‐9 could be a critical molecule for RCC invasion and metastasis not only because this MMP type destroys type IV collagen, a major component of the basement membrane , but also because type IV collagenase activity is a key determinant of the in vitro invasiveness of RCC cells and their metastatic potential . Our results are consistent with those of previous studies, which have indicated that MMP‐9 is a critical target of melatonin for regulation of RCC metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…The invasion of the basement membrane proceeds through a series of discrete steps, and the degradation of matrix in the basement membrane is largely controlled by activities of various matrix metalloproteinase (MMP) subtypes . MMPs are overexpressed in almost all cancers including RCC and are believed to be a promising therapeutic target for RCC . Among these MMPs, MMP‐2, MMP‐9, and their endogenous inhibitors, namely tissue inhibitor of matrix metalloproteinase (TIMP)‐1 and TIMP‐2, are the most crucial enzymes for controlling the degradation of the main constituent of the extracellular matrix (ECM), type IV collagen, and are deeply involved in cancer invasion and metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the systemic inflammatory response has been revealed to contribute to tumorigenesis in the last two decades. Key inflammatory pathways, such as the NF-κB [45], AP-1 [46] and STAT3 [47] pathways, are implicated in the proliferation, transformation, survival, invasion, angiogenesis, metastasis, chemoresistance and radioresistance of cancer [48]. Systemic inflammatory response, represented by elevated C-reactive protein (CRP), platelet count (PC) and erythrocyte sedimentation rate (ESR) was recently shown to predict poor survival in patients with RCC [49].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that increased phosphorylation of ERK and enhanced expression of MMP-2 or MMP-9 by treatment with gamma-aminobutyric acid (an inhibitory neurotransmitter) or knockdown of hepatocellular carcinoma-related protein (HCRP) increased the invasive activity of RCC cells [30]. Additional evidence indicates that a pyrrole-imidazole polyamide specifically targets binding sites on the MMP-9 promoter, and thereby inhibits the invasion (but not proliferation) of RCC cells [14]. We demonstrated that α-mangostin had inhibitory effects on the MMP-9 transcription activity and protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…The matrix metalloproteinases (MMPs), crucial proteolytic proteinases that allow malignant cells to access the vasculature, are a family of zinc-dependent endopeptidases with broad substrate specificities for a variety of extracellular matrix (ECM) and basement membrane proteins [14]. Aberrant regulation of the MMPs disrupts normal cellular interactions, and leads to lysis of the ECM and breaching of the basement membrane, thereby allowing malignant cells to migrate and invade distant tissues [15].…”
Section: Introductionmentioning
confidence: 99%